2006
DOI: 10.1016/j.bmcl.2005.11.018
|View full text |Cite
|
Sign up to set email alerts
|

From genome to drug lead: Identification of a small-molecule inhibitor of the SARS virus

Abstract: Virtual screening, a fast, computational approach to identify drug leads [Perola, E.; Xu, K.; Kollmeyer, T. M.; Kaufmann, S. H.; Prendergast, F. G. J. Med. Chem.2000, 43, 401; Miller, M. A. Nat. Rev. Drug Disc.2002, 1 220], is limited by a known challenge in crystallographically determining flexible regions of proteins. This approach has not been able to identify active inhibitors of the severe acute respiratory syndrome-associated coronavirus (SARS-CoV) using solely the crystal structures of a SARS-CoV cystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…EUDOC was originally devised to perform on a commodity computing cluster of loosely connected Intel Xeon** processors [2]. It has shown success in predicting drug-bound protein complexes, identifying drug leads, and reproducing crystal structures of small-molecule complexes [3,4,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…EUDOC was originally devised to perform on a commodity computing cluster of loosely connected Intel Xeon** processors [2]. It has shown success in predicting drug-bound protein complexes, identifying drug leads, and reproducing crystal structures of small-molecule complexes [3,4,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We explain, for a general audience, the computing algorithms used by EUDOC and the significance of the project. Thus, attention is given to hardware and programming details specific to EUDOC on the BG/L system, while information on the validation of the EUDOC program and its application to VS is left to other publications [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, although a number of nonpeptide inhibitors of SARS-CoV M pro have been discovered, such as bifunctional arylboronic acids, 22 isatin derivatives, 23 polyphenols, 24 etacrynic acid analogues, 25 cinanserin, 26 and other chemically diverse small molecules, 15,27,28 the lack of structure biology information on these compounds and their interactions with SARS-CoV M pro further makes the design more difficult. All the published structures up-to-date are complexed with peptidyl inhibitors through covalent bonding to SARS-CoV M pro .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] For examples, Liu et al 14 and Dooley et al 15 identified the inhibitors using 3D structure derived from molecular dynamic simulation of SARS-CoV M pro as a virtual screening target structure, while others used the pharmacophore model to predict potential inhibitors. 20,21 The discovery efforts by computer-aided drug design showed only a few cases of SARS-CoV M pro inhibition potency at micromolar range as confirmed by bioassay.…”
Section: Introductionmentioning
confidence: 99%